The effect of black glutinous rice soaking on decreasing blood sugar levels in patients’ with type 2 diabetes mellitus in Batam - Rizki Sari Utami Muchtar; Mira Agusthia; Wulan Pramadhani (Alma Ata University Press, 2021)
Background :Diabetes Mellitus, as abbreviated as DM, is a chronic disease characterized by an increase in glucose levels in the blood due to insulin damage, which can reduce the amount of glucose that enters into cells. Administration of black glutinous water soaking can reduce the need for chemical drugs, because with minimal resources it can increase the coverage and extend of nursing services without geographic boundaries.Objectives :This research aimed to determine the effect of black glutinous water soaking on the decrease in blood sugar levels in patient with type 2 diabetes.Methods :Research methods used quasi experimental. The sample consisted of 50 respondents with the inclusion criteria for type 2 DM patients who do not have gangrene complications and the data were analyzed using the Wilcoxon test.Results : The results showed that the most age in patients with type 2 diabetes mellitus is between the ages of 50-59 years (80%). Gender is most women than men, as many as 35 participants (70%. The blood sugar level of type 2 diabetes mellitus patients’ before giving black glutinous water soaking was 262.72 mg / dl, until the third week there was a significant change, where the blood sugar level had an average of 132.02 mg/dl. The statistical test results obtained between blood sugar levels up to the third week had a p-value <0.05, which is 0.00, it showed that there was an effect of giving black glutinous water soaking to a decrease in blood sugar levels in patients’ with type 2 diabetes.Conclusions : Based on this, it is recommended that the provision of black glutinous rice is one of the non pharmacological references in the implementation method of reducing blood sugar levels in clients with type 2 DM.